O método pilates sob o olhar da psicossomática - Ritter, Alice Adriana (Universidade do Vale do Rio dos Sinos, 2012)
The present paper consists of a theoretic reflection about the pilates method and its implications in emotions from the psychosomatic perspective. Our interest in the subject comes from the professional practice as a physical therapist, focused in the influence of psycho-emotional aspects shown during physical exercises and their subsequent integration with all aspects of a person’s life, including professional and social aspects. Therefore, we tried to learn, through classic literature and scientific papers, the contributions of existing theories about body movements and their psycho-emotional benefits, as the studies of W. Reich, from the oriental culture (aspects of traditional Chinese medicine), and understanding the concept of body image. From this study, we found interesting explanations about how the body movement is connected with psycho-emotional aspects, justifying physical activity as a way to influence emotions and physical appearance of a person based on their life experiences. With this knowledge, we suggest an integrative view of human being from the perspective of corporal practices.
Keywords: Método pilates; Emoções; Psicossomática; Pilates method; Emotions; Psychosomatic